A visão de alunos de gastronomia frente á realidade da profissão e a visão de Chefs profissionais - Bittencourt, Raramiz Eurípedes (2007)
Gastronomy has been more and more in evidence in Brazil in recent years. Based on this reality, this study, linked to project DIRECT Towards the language of business communication (PUC-SP/LAEL and The University of Liverpool/AELSU), presents the results of a research study developed in the area, focusing on language in the context of professional kitchens. The main aim of the study was to analyze the view about the chef profession constructed by 1st year students of a higher education Gastronomy course and by professional chefs working at renowned restaurants in the city of São Paulo. Another aim was to analyze the linguistic marks present in the discourse of a chef at work. The development of this study was theoretically supported by Halliday s Functional Grammar (1994), and by the ideational and interpersonal metafunctions proposed by him. The research corpus is composed of the answers to questions asked to 111 Gastronomy students and to 8 chefs, as well as the audio recording of a chef commanding his team. The computer tool WordSmith Tools (Scott, 1999) was used. This tool offers resources to analyze several language aspects; with it, it was possible to analyze the frequencies of some lexical items that reveal expectations and aspirations of the pre-service concerning the reality presented by professionals who work in the area and their language in service. Thus, this study provides information that reveal particular aspects of an age-old profession that has been much valued nowadays, desired by youths who see in the career many opportunities, and who are willing to face the obstacles inherent in the area